A Common Mutation of the Insulin Receptor Substrate-1 Gene Is A Risk Factor for Coronary Artery Disease - Baroni, Marco Giorgio; D’Andrea, Maria Pina; Montali, Anna; Pannitteri, Gaetano; Barillà, Francesco; Campagna, Filomena; Mazzei, Ercole; Lovari, Sarah; Seccareccia, Fulvia; Campa, Pietro Paolo; Ricci, Giorgio; Pozzilli, Paolo; et al. (Arteriosclerosis, thrombosis, and vascular biology, 1999)
Insulin resistance is associated with increased risk of atherosclerosis. Insulin receptor substrate-1 (IRS-1) plays a key role in tissue insulin sensitivity. A common mutation (G972R) of the IRS-1 gene has been shown to impair IRS-1 function, and it has been associated with reduced insulin sensitivity and lipid abnormalities. This led us to investigate the role of the G972R mutation in predisposing individuals to coronary artery disease (CAD). The DNA of 318 subjects with angiographically documented coronary atherosclerosis (>50% stenosis) and 208 population control subjects was analyzed for the presence of the G972R mutation. This mutation was detected by nested polymerase chain reaction and Bst NI restriction enzyme digestion. The frequency of the G972R mutation was significantly higher among patients with CAD than controls (18.9% versus 6.8%, respectively;P<0.001). After controlling for other coronary risk factors, the relative risk of CAD associated with the G972R mutation was 2.93 (95% CI 1.30 to 6.60;P<0.02) in the entire cohort. This risk was found to be even higher in the subgroups of obese subjects (odds ratio [OR] 6.97, 95% CI 2.24 to 21.4;P<0.001) and subjects with clinical features of insulin resistance syndrome (OR 27.3, 95% CI 7.19 to 104.0;P<0.001). The IRS-1 gene variant was associated with a higher frequency of diabetes mellitus (14.9% among carriers versus 6.5% among noncarriers;P<0.01) and with a 60% increase of plasma total triglycerides (P<0.001). Also, plasma concentrations of total cholesterol and the ratio of total cholesterol to HDL cholesterol were significantly (P<0.001) higher among carriers than noncarriers, although to lesser a extent. These effects were independent of CAD status. The G972R mutation in the IRS-1 gene was found to be a significant independent predictor of CAD. Moreover, this mutation greatly increased the risk of CAD in obese subjects and in patients with the cluster of abnormalities of insulin resistance syndrome. Besides the increased frequency of diabetes, carriers showed a more atherogenic lipid profile, suggesting a potential role of the IRS-1 gene in the pathogenesis of lipid abnormalities associated with CAD.